The first species of Eutheimorphus Franz & Löbl in Thailand (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
Up to date, Eutheimorphus Franz & Löbl included a sole species known from a holotype male collected in Sabah, Borneo. An occurrence of this enigmatic and extremely rare genus in Thailand is reported, and Eutheimorphus thailandicus sp. n. is described. Among diagnostic characters are unique grooves on the head and a symmetrical (in contrast to strongly asymmetrical in E. paradoxus Franz & Löbl) set of endophallic sclerites.